Need of vocational high school based on local potential for regional development in Cilacap District - Widi Lesmana; Pardjono Pardjono (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
This study intends to: (1) describe regional development programs, (2) determine local potential, (3) describe the level of alignment of the current spectrum of expertise and make a spectrum of expertise Vocational High Schools based local potential in the Cilacap District. Descriptive research was used in this study. The research site was carried out in the Cilacap Regency area. The data sources used are secondary data sources, namely the use of data through official documents such as the Rencana Tata Ruang Wilayah (RTRW), Rencana Pembangunan Jangka Menengah Daerah (RPJMD), Cilacap Regency in the 2017 Figures and the Cilacap Regency Economic Census in 2016. Analysis of official documents are used to achieve the research objectives. The validity of the documents carried out is the provision of a wet stamp from the related agency. The results of this study include: (1) the development program planned for the development of local potential in the Cilacap Regency area is listed on the 4th mission of regional development, namely